An Analysis of Students Errors In Writing Recount Text - Lestari, Eftaria Agus; Yolanda, Alvina; Yassin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aims of this research were find out the types of errors in writing recount text, the research and the sample was tenth grade students ofÂ X. In this study, descriptive qualitative research was the methodology employed.Â The study's results, which examined different forms of student errors, were obtained from their recount texts in the form of essay tests. In order to determine how the errors happened, the researcher also conducted interviews to gather information. The study's findings showed that MA Al Ishlah students continued to make mistakes in their recount texts. It was evident that the mistakes made by the students included addition, subtraction, distortion, and disarray. These mistakes resulted from students applying the rules of their first language too broadly (intralingual), from them generalizing the rule and applying it insufficiently (interlingual), from their lack of motivation to write with correct English grammar (carelessness), and from the methods used to present the material.